2005
DOI: 10.1016/j.trstmh.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern of severe Plasmodium falciparum malaria in Sudan in an area characterized by seasonal and unstable malaria transmission

Abstract: A hospital-based study was carried out in Gedarif town, eastern Sudan, an area of markedly unstable malaria transmission. Among the 2488 diagnosed malaria patients, 4.4% fulfilled the WHO criteria for severe malaria, and seven died of cerebral malaria. The predominant complication was severe malarial anemia (45.4%), followed by convulsions (21%), cerebral malaria (16. 4%) and hypotension (11.8%). Severe malaria was recognized in all age groups, but 44.5% of patients were aged 2 to 4 years. The mean ages of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 18 publications
6
40
1
Order By: Relevance
“…We found no correlation between MOI and age, unlike in previous reports from malaria-hyperendemic regions (Konate et al 1999;Ntoumi et al 1995). However, in this area, both UM and SM affect all age groups, but SM is more common in younger patients (Giha et al 2005). Furthermore, there was no correlation between pretreatment parasitemia and clone number as mentioned in other studies (Henning et al 2004).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We found no correlation between MOI and age, unlike in previous reports from malaria-hyperendemic regions (Konate et al 1999;Ntoumi et al 1995). However, in this area, both UM and SM affect all age groups, but SM is more common in younger patients (Giha et al 2005). Furthermore, there was no correlation between pretreatment parasitemia and clone number as mentioned in other studies (Henning et al 2004).…”
Section: Discussioncontrasting
confidence: 94%
“…This study was carried out over two consecutive malaria seasons (September-January), between 2000 and 2002. The clinical and epidemiological pattern of SM was presented elsewhere (Giha et al 2005). The P. falciparum is the predominant species (98%), and the Anopheles arabiensis is the sole vector.…”
Section: Study Areamentioning
confidence: 99%
“…The moderate, seasonal, and markedly unstable Plasmodium falciparum malaria infection is transmitted mainly by Anopheles arabiensis, and the entomological inoculation rate (EIR) is very low. The clinical patterns of SM in the area have been previously reported (Giha et al 2005). …”
Section: Study Areamentioning
confidence: 88%
“…The commonest clinical manifestation was fever with chills and rigors (100%), headache (25.5%)'vomiting (22.2%) jaundice (15.5%). 8 Commonest sign being splenomegaly (86.7%) followed by pallor (46.7%) and icterus (13.3%) . These findings are comparable with other studies like Oh MD et al, Song HH et al Giha HA et al Grobusch MP et al Trampuz A et al who found that fever with chills was the most common symptom found followed by headache, vomiting and jaundice.…”
Section: Discussionmentioning
confidence: 99%